Expression of cytokinin responsive and ethylene biosynthesis genes in rice callus with different regeneration rates - Syafira Fatihatul Husna; Parawita Dewanti; Bambang Sugiharto; Wahyu Indra Duwi Fanata (Indonesian Journal of Biotechnology, 2022)
This study aimed to investigate the correlation between callus regeneration rate and the expression of several genes responsible for cytokinin response and ethylene biosynthesis in the Ciherang, Mentik Wangi Susu, Hwayoung and Tarabas rice varieties. The callus regeneration rate of each rice variety was in vitro tested using N6 media, while the gene expression during the callus regeneration stages was examined using quantitative real‐time PCR (qRT‐PCR). Our results showed that the callus of Ciherang and Mentik Wangi Susu showed earlier green spot formation that then turned brown at a later stage, resulting in a low regeneration rate. While Hwayoung and Tarabas showed late green spot formation, high shoot regeneration was observed in both calluses. Gene expression analysis of regeneration media‐grown calluses showed that two cytokinin‐responsive genes, OsRR2 and OsRR6, were highly expressed in the Ciherang and Hwayoung callus, respectively. We also observed that ethylene biosynthesis genes such as OsACS1 and OsACO1 were highly expressed in the Mentik Wangi Susu and Hwayoung callus, respectively. Moreover, the expression of OsBBM1 was high in Hwayoung and Tarabas. Thus, the positive correlation between the expression of cytokinin‐responsive and ethylene biosynthesis genes with somatic embryogenesis activity likely depends on the induction level of OsBBM1.